Long term trends in atmospheric concentrations of polycyclic aromatic hydrocarbons and nitropolycyclic aromatic hydrocarbons: A study of Japanese cities from 1997 to 2014. (February 2018) - Hayakawa, Kazuichi; Tang, Ning; Nagato, Edward Gou; Toriba, Akira; Sakai, Shigekatsu; Kano, Fumio; Goto, Sumio; Endo, Osamu; Arashidani, Kei-ichi; Kakimoto, Hitoshi
Abstract: Total suspended particulate matter (TSP) was collected during the summer and winter in five Japanese cities spanning Hokkaido to Kyushu (Sapporo, Kanazawa, Tokyo, Sagamihara and Kitakyushu) from 1997 to 2014. Nine polycyclic aromatic hydrocarbons (PAHs) with four to six rings, including pyrene (Pyr) and benzo[ a ]pyrene (BaP), were identified using high-performance liquid chromatography (HPLC) with fluorescence detection. Two nitropolycyclic aromatic hydrocarbons (NPAHs), 1-nitropyrene (1-NP) and 6-nitrobenzo[ a ]pyrene (6-NBaP), were identified by HPLC with chemiluminescence detection. A comparison of PAH and NPAH concentrations and [NPAH]/[PAH] ratios such as [1-NP]/[Pyr] and [6-NBaP]/[BaP] revealed the following characteristics in the five cities: (1) In Sapporo, Kanazawa, Tokyo and Sagamihara, the concentrations of PAHs and NPAHs were high at the beginning of the sampling period and then steadily decreased, with NPAHs decreasing faster than PAHs. The large initial [1-NP]/[Pyr] ratios suggest that the major contributor was automobiles but subsequent decreases in this ratio suggest decreased automobile contributions. (2) By contrast, PAH concentrations in Kitakyushu did not decrease during the sampling period, though concentrations of NPAHs decreased. The consistently smaller [1-NP]/[Pyr] ratio and larger [6-NBaP]/[BaP] ratio in Kitakyushu suggests that the major contributor of PAHs was not automobiles but iron manufacturing which uses a large amount of coal. The sudden increase in atmospheric PAH concentrations in the winter of 2014 may also be due to iron manufacturing. Graphical abstract: Image 1 Highlights: Trends in PAH and NPAH concentrations between 1997 and 2013 were studied. Commercial cities showed steady decreases in NPAH/PAH ratio concentrations. Iron manufacturing accounted for the steady NPAH/PAH ratios in one city. Changes in PAH and NPAH concentrations followed tighter restrictions on emissions. Abstract : Atmospheric concentrations of polycyclic aromatic hydrocarbons and nitropolycyclic aromatic hydrocarbons decreased in Sapporo, Kanazawa, Tokyo and Sagamihara from 1997 to 2014 as a result of controls on PM and NOx emissions from automobiles, but did not in Kitakyushu where the major contributor is iron-manufacturing, which consumes a large amount of coal.